The Types of Derivational Suffixes Found in The Dry Novel by Jane Harper - Pramesti, Ni Made Dian; Nova Winarta, Ida Bagus Gde (Humanis; Vol 28 No 1 (2024), 2024)
The study focused on analysing the types of derivational suffixes. The data was taken from The Dry by Jane Harper and analysed by using the theory from Plag (2003) and Carstairs-Mccarthy (2002) . The data collected was analysed by using a descriptive qualitative method. The results of this study were explained using both formal and informal methods. The findings showed that there are four types of derivational suffixes found in this novel, such as nominal suffixes, verbal suffixes, adjectival suffixes, and adverbial suffixes. The total of the data found in this study is 194 data which consist of nominal suffixes with 66 data. The second, in verbal suffixes with 1 data. Next, adjectival suffixes with 69 data. The last suffix is adverbial suffixes with 58 data.